2012
DOI: 10.1289/ehp.1103696
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hexachlorobenzene (HCB), Dichlorodiphenyltrichloroethane (DDT), and Dichlorodiphenyldichloroethylene (DDE) with in Vitro Fertilization (IVF) Outcomes

Abstract: Background: Hexachlorobenzene (HCB), dichlorodiphenyltrichloroethane (DDT), and dichlorodiphenyldichloroethylene (DDE) are persistent chlorinated pesticides with endocrine activity that may adversely affect the early stages of human reproduction.Objective: Our goal was to determine the association of serum levels of HCB, DDT, and DDE with implantation failure, chemical pregnancy, and spontaneous abortion in women undergoing in vitro fertilization (IVF) from 1994 to 2003.Methods: Levels of HCB and congeners of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 28 publications
2
25
0
2
Order By: Relevance
“…Our findings are relatively consistent with studies of women undergoing assisted reproductive technologies that can examine associations with early reproductive outcomes (e.g., fertilization, cleavage, implantation) that are not observable in the general population. For example, evidence of negative associations between TTP and serum concentrations of HCB and PCB 118 in women is consistent with findings for implantation failures associated with these exposures among women undergoing assisted reproductive technologies (Mahalingaiah et al 2012; Meeker et al 2011). Although speculative, these findings suggest that associations between these chemicals and longer TTPs may reflect, in part, diminished implantation success.…”
Section: Discussionsupporting
confidence: 66%
“…Our findings are relatively consistent with studies of women undergoing assisted reproductive technologies that can examine associations with early reproductive outcomes (e.g., fertilization, cleavage, implantation) that are not observable in the general population. For example, evidence of negative associations between TTP and serum concentrations of HCB and PCB 118 in women is consistent with findings for implantation failures associated with these exposures among women undergoing assisted reproductive technologies (Mahalingaiah et al 2012; Meeker et al 2011). Although speculative, these findings suggest that associations between these chemicals and longer TTPs may reflect, in part, diminished implantation success.…”
Section: Discussionsupporting
confidence: 66%
“…Environmental contaminants might also affect ovarian response during OS [29][30][31]. Thus, Alviggi et al in a retrospective study showed that elevated intrafollicular levels of benzene were associated with a decreased number of oocytes retrieved and embryos available for transfer [29], and it is currently believed that benzene leads to transduction deficiency in the FSHR.…”
Section: Poseidon Groups 1 Andmentioning
confidence: 99%
“…Due to the ART clinic population’s higher frequency of infertility issues relative to the general population, these clinics provide a setting in which to conduct such studies with reliable statistical power. Persons seeking treatment at ART clinics have already served as study populations in epidemiology investigations designed to determine potential adverse effects of exposures to chemicals on female (Ehrlich et al, 2012; Johnson et al, 2012; Mahalingaiah et al, 2012) and male reproductive health (Dodge et al 2015; Meeker et al 2010; 2011). Recent evidence also suggests that it is similarly feasible to recruit women and men from infertility clinics to participate in longitudinal investigations of magnetic field exposure and reproductive health (EPRI, 2012; Lewis et al, 2015b).…”
Section: Recommendations For Future Studiesmentioning
confidence: 99%